Enabling ultra-flexible inorganic thin-film-based thermoelectric devices by introducing nanoscale titanium layers - Ming Tan; Xiao-Lei Shi; Wei-Di Liu; Yong Jiang; Si-Qi Liu; Tianyi Cao; Wenyi Chen; Meng Li; Tong Lin; Yuan Deng; Shaomin Liu; Zhi-Gang Chen (Nature Communications)
Abstract Here, we design exotic interfaces within a flexible thermoelectric device, incorporating a polyimide substrate, Ti contact layer, Cu electrode, Ti barrier layer, and thermoelectric thin film. The device features 162 pairs of thin-film legs with high room-temperature performance, using p-Bi0.5Sb1.5Te3 and n-Bi2Te2.7Se0.3, with figure-of-merit values of 1.39 and 1.44, respectively. The 10 nm Ti contact layer creates a strong bond between the substrate and the Cu electrode, while the 10 nm Ti barrier layer significantly reduces internal resistance and enhances the tightness between thermoelectric thin films and Cu electrodes. This enables both exceptional flexibility and an impressive power density of 108 μW cm−2 under a temperature difference of just 5 K, with a normalized power density exceeding 4 μW cm−2 K−2. When attached to a 50 °C irregular heat source, three series-connected devices generate 1.85 V, powering a light-emitting diode without the need for an additional heat sink or booster.